Interest and Learning Outcome of Learning Material Long Jump Squat Style (Tuck) Through Rubber Rope Assistance - Alam, Syamsu (International Journal of Management and Education in Human Development, 2021)
The purpose of the study is to find out How the implementation of tools to help Ropes Rubber in increasing the interest and the results of PJOK learning material jump much style squat (tuck) students grade VII.1 SMP Negeri 9 Kendari and Do means of auxiliary rope rubber can increase the interest and the results of learning PJOK materials jump far Squat style (tuck) class VII.1 students of SMP Negeri 9 Kendari . This research was conducted in the School Class VII.1 SMP Negeri 9 Kendari District of Kadia , Kendari . The location of this research was determined because it took into account the ease of cooperation between researchers, the school, and the object being studied as well as time and cost savings because the research location is a place for researchers to teach. The research will be carried out in semester 1 , starting from October to December 2019. Data in the form of observations or observations are classified as qualitative data. This data is interpreted and then connected with quantitative data (tests) as a basis for describing the success of the learning implementation that has been carried out. The test results data were analyzed descriptively, namely by comparing the test results between cycles . Based on the results of research on the application of Rubber Rope aids to Class VII.1 students of SMP Negeri 9 Kendari for the 2019/2020 academic year . Results of studying cognitive eyes of subjects PJOK students Class VII.1 SMP Negeri 9 Kendari on material long jump squat style (tuck) increased by applying tools rubber strap . This can be seen from the average value of the class there was an increase in the first cycle of 77.4 ; and in cycle II 86 . For students who finished studying (completeness score 7 6) in the first cycle 72.22% after reflection there were 6 students who did not complete (test score below 76 ) , but overall their learning outcomes had increased when viewed from the percentage of students' completeness , and at the second cycle test became 100 % after the second reflection there were 0 students who did not complete (the test score was below 76 ). To increase interest and learning outcomes of PJOK material long jump squat style (tuck) using a rubber rope tool is that the teacher must be skilled in applying the rubber rope tool and adapted to the situation and condition of the students.